Highly Nonstoichiometric YAG Ceramics with Modified Luminescence Properties. (20th January 2023) - Cao, Weiwei; Becerro, Ana Isabel; Castaing, Victor; Fang, Xue; Florian, Pierre; Fayon, Franck; Zanghi, Didier; Veron, Emmanuel; Zandonà, Alessio; Genevois, Cécile; Pitcher, Michael J.; Allix, Mathieu
Abstract: Y3 Al5 O12 (YAG) is a widely used phosphor host. Its optical properties are controlled by chemical substitution at its YO8 or AlO6 /AlO4 sublattices, with emission wavelengths defined by rare‐earth and transition‐metal dopants that have been explored extensively. Nonstoichiometric compositions Y3+x Al5‐x O12 ( x ≠ 0) may offer a route to new emission wavelengths by distributing dopants over two or more sublattices simultaneously, producing new local coordination environments for the activator ions. However, YAG typically behaves as a line phase, and such compositions are therefore challenging to synthesize. Here, a series of highly nonstoichiometric Y3+x Al5‐x O12 with 0 ≤ x ≤ 0.40 is reported, corresponding to ≤20% of the AlO6 sublattice substituted by Y 3+, synthesized by advanced melt‐quenching techniques. This impacts the up‐conversion luminescence of Yb 3+ /Er 3+ ‐doped systems, whose yellow‐green emission differs from the red‐orange emission of their stoichiometric counterparts. In contrast, the YAG:Ce 3+ system has a different structural response to nonstoichiometry and its down‐conversion emission is only weakly affected. Analogous highly nonstoichiometric systems should be obtainable for a range of garnet materials, demonstrated here by the synthesis of Gd3.2 Al4.8 O12 and Gd3.2 Ga4.8 O12 . This opens pathways to property tuning by control of host stoichiometry, and the prospect of improved performance or new applications for garnet‐type materials. Abstract : A family of highly nonstoichiometric Y3 Al5 O12 (YAG) ceramics is isolated by advanced melt‐quenching methods. In these materials, rare‐earth dopants can populate two crystallographic sublattices, providing a mechanism for luminescence color tuning that is not available to conventional stoichiometric YAGs. The concept is generalized to other garnet ceramics including GAG and GGG, opening new avenues for exploration in this important materials class.